2017
DOI: 10.1007/s11540-018-9366-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Consequences for Potato Production: a Review of Tolerance to Emerging Abiotic Stress

Abstract: Potato is a major global crop that has an important role to play in food security, reducing poverty and improving human nutrition. Enhanced atmospheric CO 2 concentrations provide an opportunity to increase potato yields in the future, but this will only be possible if the potato crop can cope with the other consequences of climate change caused by this rise in CO 2 . While climate change may impact biotic stress either positively or negatively, abiotic stresses are likely to be greatly increased and become a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 171 publications
(145 reference statements)
3
61
0
3
Order By: Relevance
“…The capacity of photosynthesis was decreased because the inhibition of CO 2 fixation and chlorophyll loss [9], carbon transport is also sensitive to high temperature which results in starch accumulation decreased [10], elevated temperature also have negative impacts on potato skin finish [11]. Additionally, high temperatures during tuber maturation have a negative effect on tuber dormancy and can cause the potatoes to start sprouting [12]. Due to the global climate warming resulting in temperature rising, it is strongly necessary to raise heat-tolerant potato varieties to cope with elevated temperature that sustain high yields under 4 these conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of photosynthesis was decreased because the inhibition of CO 2 fixation and chlorophyll loss [9], carbon transport is also sensitive to high temperature which results in starch accumulation decreased [10], elevated temperature also have negative impacts on potato skin finish [11]. Additionally, high temperatures during tuber maturation have a negative effect on tuber dormancy and can cause the potatoes to start sprouting [12]. Due to the global climate warming resulting in temperature rising, it is strongly necessary to raise heat-tolerant potato varieties to cope with elevated temperature that sustain high yields under 4 these conditions [7].…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating more organic material like composts and green manures [36], the soils themselves can be managed to increase their fertility, workability and how much moisture they hold. Likewise, encouraging the plants to develop deeper roots-by providing irrigation in large sustained drenchings rather than lots of small sprinklings-means that drying out of surface soils during a drought will do less damage [37].…”
Section: * * *mentioning
confidence: 99%
“…These studies have focused on abiotic factors, such as waterlogging, drought, and temperature fluctuations related to climate change [19,20]. Studies in the literature have reported that, in many cases, the most efficient and least costly response to stress is the use of new adapted varieties [21] and, in this respect, a large availability of germplasm could facilitate the task.…”
Section: Introductionmentioning
confidence: 99%